JOB STRESS AND COPING AMONG FISHERMEN - Jacob, Janella Mariam; George, Linu Sara; Savitha (Journal of Health and Allied Sciences NU, 2013)
Introduction: Fishing in Indian villages is considered one of the major occupations for the villagers. The work related health problems encountered by fishermen are vast. Long hours, extreme weather and working with heavy machinery contribute to a high mortality rate in fishermen. Despite a long standing acknowledgement of the dangers and mortality associated with fishing, there has been little research in this fieldObjectives: The objectives of the study were to: assess the job stress and coping among fishermen, find the relationship between job stress and coping, find the association between job stress, coping and demographic variables such as age, religion, marital status, type of family, education, monthly income and work experience.Materials and Methods: A descriptive survey was under taken among 140 fishermen using structured questionnaire. SPSS 16.0 software was used for data analysis. Frequency, percentage, Pearsons product moment correlation and Chi-square were used.Results: Majority of the subjects had moderate stress (62.1%) and moderate cope (91.4%). It is found in the study that there is significant 2 relationship between job stress and coping. There is significant association between job stress and work experience (? = 6.90, p<0.05).Conclusion: Fishermen who work for long hours in the sea without any contact with their families are prone to problems with their work and their personal life as it is unsafe at sea.
Keywords: Fishermen; job stress; coping